2023
DOI: 10.1038/s41598-023-39658-6
|View full text |Cite
|
Sign up to set email alerts
|

Social support, oral health knowledge, attitudes, practice, self-efficacy and oral health-related quality of life in Chinese college students

Abstract: Oral health is crucial for health-related quality of life. However, the research on the factors affecting oral health status is not comprehensive enough. This investigation aimed to evaluate the multifaceted determinants of college students’ oral health status and explore the impact of social support, oral health literacy, attitudes, behaviors, and self-efficacy on OHRQoL. By surveying 822 students from a university. Baseline data included sociodemographics (gender, age), social support (MSPSS scale), oral hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…16 These results show that dental health education (DHE) can reduce the debris index so that students have started to know new information and learn to understand the new object, namely how to maintain dental and oral hygiene. 15 These results are in line with research conducted by Wang et al (2023) which shows that dental students have better knowledge, attitudes and oral health behavior compared to non-dental students. This research also found that oral health education can increase the frequency of brushing teeth and the use of dental floss in both groups of students .…”
Section: B Debris Indexsupporting
confidence: 74%
“…16 These results show that dental health education (DHE) can reduce the debris index so that students have started to know new information and learn to understand the new object, namely how to maintain dental and oral hygiene. 15 These results are in line with research conducted by Wang et al (2023) which shows that dental students have better knowledge, attitudes and oral health behavior compared to non-dental students. This research also found that oral health education can increase the frequency of brushing teeth and the use of dental floss in both groups of students .…”
Section: B Debris Indexsupporting
confidence: 74%
“…Further analysis is needed to obtain this information in the future. Additionally, oral health literacy, including exercise habits and eating a balanced diet is related to oral health knowledge 25 . Therefore, our results are consistent with the findings of a previous study and provide useful information about raising awareness regarding oral frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The field of information and communication technology (ICT) has experienced rapid expansion, and mobile phone apps are now frequently used not only as communication tools but also to assist with internet access, email, reminders, and other daily activities. It has been discovered that mobile phone app-assisted educational interventions are more effective than traditional ones [15]- [17]. The findings of the systematic investigations led to this conclusion.…”
Section: Introductionmentioning
confidence: 95%